PERMODELAN TARIKKAN PERJALANAN TERHADAP PUSAT PENDIDIKAN SMPN 10 SAMARINDA - DIETYA SILVA, IRA (KURVA S JURNAL MAHASISWA, 2014)
Area education of SMPN 10 Samarinda represent area which is visited so that causing it attraction attraction journey of which can encumber band jalaur go to centre of activities.Problem that happened at area of SMPN 10 Samarinda have the following Formula Problem 1. As Model Attraction Journey in SMPN 10 Samarinda 2. How Pattern Journey in SMPN 10 Samarinda.For data matching with the problem of accurate by hence researcher use technique data collecting of spreading 150 Sheet of Kuesioner and by holding an interview with family done with a view to get direct Information as for questionnaire at Sheet of Kuesioner and Program of Softwere SPSS used to do Calculation.            Of Visitor data in SMPN 10 Samarinda there are 30 Class with amount of pupil 1005 and teacher 56 soul with total entirety 1061. Result of obtained data of kuesioner there are 2 journey attraction model that is Distance Journey ( X2), Way Of Going to Journey ( X3) so that variable tied to have equation of Y regrensi= 0,271 + 0,026(X2 + 0,839(X3) and Value Test R ( Coefficient of Kolerasi doubled = 0,739. Menunjukan mount [relation/link] of variable dependen ( Variable tied) with independent Variable ( Free Variable) [at] storey;level of Kolerasi Strong [of] menunjukan that 73,9 % from ( variable tied) can be explained by perunahan in Variable Apart Journey ( X2), Way Of Going to Journey ( X3).